A aplicação do princípio da retroatividade à nova lei de improbidade administrativa - Façanha, Sofia Scopel (2023)
The present work proposes to analyze the ARE 843989, responsible for establishing the thesis of general repercussion for Theme 1199, which is of great importance for the maintenance of legal security in the country, in addition to dealing with the fight against acts of corruption and improbity practiced by agents public. To this end, an overview of Public Administration and its fundamental principles was drawn, as well as the law of administrative improbity and its main changes with Law 14.230/2021. Next, we seek to understand the rationale for the (ir)retroactive application of the most tolerant rules to the defendant in administrative law. Finally, the grounds for ARE 843989 are examined